REINTERPRETASI “MAQOM KAROMAH” DI TENGAH MASYARAKAT DALAM KAJIAN SEMIOTIK CHARLES SANDERS PEIRCE - Zuhri Fahruddin,; Karmuji Abu Safar, (JOEL: Journal of Educational and Language Research, 2021)
People often clash the term "Maqom Karomah" which is different from the original sentence, making the meaning shift away from the original meaning. Starting from the object in the form of material that has reason, the object turns into material that has no sense, because of different cultures and values in society. This research is an analysis of a text/sentence using Charles Sanders Pierce's semiotics, Charles Sanders Pierce's model is known as Triadic (Triangle Meaning Semiotics), and the interpretant (interpretant).